Comparison of prednisolone and alternative glucocorticoid dosing protocols for canine hypoadrenocorticism: insights from a survey-based study - Emming, Christin; Geks, Anna Karoline; Sajadihezaveh, Sajedeh; Rieker, Thomas; Brutsche, Johannes; Volk, Holger Andreas; Rieder, Johanna (Frontiers in Veterinary Science, 2025)
ObjectivesThe aim of the study was to analyze glucocorticoid (GC) dosing protocols in dogs with hypoadrenocorticism (HA), and to identify predictors for optimal clinical outcomes during both the acute and chronic phases of the disease, as well as during long-term therapy.MethodsThis observational cross-sectional study utilized a case-based online questionnaire. Practicing veterinarians across Germany were invited to participate. The survey collected data in the disease course and follow-ups. Responses were analyzed using descriptive statistics, single and multiple comparisons, and a multivariable logistic regression model.ResultsFor 103 dogs the questionnaire was fully completed and analyzed. Of these, 85 dogs (82.5%) were hospitalized, and they received either prednisolone (52.9%), dexamethasone (31.8%) or hydrocortisone (11.8%). Hydrocortisone therapy was associated with a shorter hospitalization time and faster normalization of electrolytes compared to prednisolone. Follow-up data were available for 85 dogs, with 82.35% (n = 70/85) achieving an optimal or well-adjusted clinical outcome. Multivariable logistic regression analysis indicated that the eukalemic and eunatremic form was significantly less associated with the presence of azotemia and the occurrence of an acute adrenal crisis. Dividing the daily GC dosage was associated with poorer clinical outcomes and a reduced likelihood of achieving optimal medication adjustment.ConclusionOur findings provide new, relevant recommendations for the therapeutic management of HA in dogs. Hydrocortisone appears to be a promising treatment for managing HA during hospitalization, highlighting its potential use in clinical practice. Once-daily administration of prednisolone is advisable for long-term therapy. To achieve the best possible outcome, implementing an optimal treatment protocol is essential, which veterinarians should tailor based on the needs of both owners and animals. The main limitations of the study include its retrospective nature and the limited number of participants. Future studies, particularly prospective ones, could further validate the beneficial effects of hydrocortisone and evaluate long-term therapy in comparison to prednisolone.